Natural theology, revealed theology and mystic theology: Philosophical reflections, starting from Saint Thomas Aquinas and Saint John of the Cross - González Suárez, Lucero (Cuestiones Teológicas, 2021)
What kind of theological discourse about God has preeminence, by virtue of his essential character? The purpose of this article is to answer that question. The thesis to be demonstrated is that, while natural theology and revealed theology (whose masterful synthesis is the work of Saint Thomas Aquinas) are discourses on God, mystical theology of Saint John of the Cross is a discourse from God. Ultimately, the purpose of this reflection is to show that, from a phenomenological point of view, the mystical theology  is superior to natural theology and revealed theology. Since, instead of degrading the mystery of God as a concept, it makes it understandable in a way that preserves its sacredness.
Keywords: Theology; Mysticism; Natural theology; Revealed theology; Saint Thomas Aquinas; Saint John of the Cross; Metaphysics; God